An evaluation of the libraries in engineering colleges and universities in Metro Manila - Conejo, Fresca P. (1998)
This study is an evaluation of the twenty-five engineering libraries of colleges and universities in Metro Manila. The ultimate goal of the study is to find out if the participating libraries complied with the standards set by the Technical Panel for Engineering Architecture, and Maritime Education (TPEAME). Conducted during the second semester of school year 1996-1997, a two-part questionnaire was used to gather data on the present status of the engineering libraries supplemented by direct observation and interviews. Findings were anlyzed and compared against the TPEAME standards.